Relationship assessment between mood disorders, headaches, and temporomandibular disorders in healthcare workers post-COVID-19 pandemic - Neves,Rodrigo Falcão (2023)
Abstract Objectives: To evaluate the relationship between depression, anxiety, and stress levels, headaches, and symptoms of temporomandibular joint disorders in healthcare professionals in a post-pandemic setting. Methods: A cross-sectional study conducted through an online questionnaire was distributed among healthcare professionals in Mainland Portugal. The sample’s characterization was undertaken according to sociodemographic parameters. The following assessment instruments were used: 21-item Depression, Anxiety, and Stress Scale (DASS-21) for emotional parameters, namely depression, anxiety, and stress; International Classification of Headache Disorders (ICHD-3) for headache disorders; Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) for temporomandibular joint dysfunction symptoms. Inferential analysis was performed using phi, Cramer’s V, and gamma tests. Results: The sample comprised 118 individuals (93.2% female, 6.8% male). Results showed a prevalence of 38.1% for depression, 51.7% for anxiety, and 39.8% for stress. Regarding headaches, a prevalence of 62.7% was reported. Symptoms of temporomandibular disorders had a prevalence of 50%. Significant differences were found between headache and stress (p=0.034), headache and temporomandibular joint disorders symptoms (p=0.002), and symptoms of temporomandibular disorders and depression (p=0.009), anxiety (p=0.003), and stress levels (p=0.014). Conclusions: There seems to be a positive correlation between headaches and stress levels, between temporomandibular disorders symptoms and all psychosocial parameters, and between temporomandibular disorder symptoms and headaches. Data suggests that these symptoms worsened after the pandemic